2001
DOI: 10.1023/a:1013382832091
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The sustained delivery of BMP-2 based on the biodegradable PLGA microsphere system resulted in faster and more complete bone healing in the animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Sustained delivery vehicles for recombinant proteins have been studied previously, primarily using 125 I-labeled proteins [15, 50, 5257]. In this study, the protein release kinetics from the collagen sponge were similar to those reported previously in ectopic bone formation models, in which the retention half-life ranged from several hours to several days [5861].…”
Section: Discussionsupporting
confidence: 76%
“…Sustained delivery vehicles for recombinant proteins have been studied previously, primarily using 125 I-labeled proteins [15, 50, 5257]. In this study, the protein release kinetics from the collagen sponge were similar to those reported previously in ectopic bone formation models, in which the retention half-life ranged from several hours to several days [5861].…”
Section: Discussionsupporting
confidence: 76%
“…Direct application is via delivery of BMP2 either locally or systemically. The local and sustained in vivo release of BMP2 based on the biodegradable PLGA microsphere system [35] and apatite-coated PLGA/nanohydroxyapatite particulates [36] resulted in faster and more complete bone healing in critical-size calvarial defects. Subcutaneous injection of BMP2 for three days post-operatively enhanced undifferentiated human ASC-seeded PLGA constructs in the repair of critical-size calvarial defects in a nude mouse model [15].…”
Section: Discussionmentioning
confidence: 99%
“…During bone repair, BMP-2 is expressed early during the early inflammatory phase, and later in the process during osteogenesis[37]. Thus, it is not surprising that many reports have shown that bone regeneration can be enhanced by sustained release of BMP-2[38, 39]. The data presented here showed sustained release of each growth factor for over 30 days (figures 6b, 7b, and 8b), and the ability to modulate the release profiles based on the properties of the mineral coating.…”
Section: Discussionmentioning
confidence: 99%